A simulation and experiment coassisted learning platform for understanding electromagnetic interaction in a smart grid. Issue 5 (6th January 2021) - Huang, Qi; Xu, Xinhao; Li, Jian; Zhang, Zhenyuan; Hu, Weihao
Abstract: An innovative current measurement method in power systems has attracted more attention from both the industry and academia. Nevertheless, students can feel challenged when assigned to learn new concepts with the currently already difficult engineering courses. Therefore, in this paper, a training platform is designed based on finite element analysis simulation and laboratory experiments. With this training platform, simple and effective simulations and experiments can be performed. In addition, extended applications of this training platform are presented such as design of the magnetic shielding structure, magnetic flux density visualization and calculation of overhead power lines. This design can help engineering students to better understand the application of electromagnetics and the novel current measurement research field.